Subgenual cingulate cortex and personality in chimpanzees (Pan troglodytes) - Blatchley, Barbara J. (2010)
Animals vary in their dispositions, abilities, and moods and demonstrate characteristic behavior patterns that remain consistent across situation and time. This study describes the relationship between measures of personality in the chimpanzee and the structure of the subgenual cingulate cortex (SGCC). Measures of individual traits and personality factors (dominance, extraversion, conscientiousness, and agreeableness) and assessments of percentage of SGCC gray matter (PGM) and asymmetry taken from MRI scans were obtained for 74 chimpanzees housed at the Yerkes National Primate Research Center. PGM in the SGCC was significantly higher for females than for males and was significantly correlated with two personality factors (dominance and conscientiousness) in male apes. There was also a population-level leftward asymmetry in the SGCC. These results are discussed in terms of current models of SGCC function, which suggest that this area may play a role in the biological foundation of personality.